Low-cost and simple PCR process for access to molecular diagnosis of HTLV-1/2 in low-resource countries - Ducasa, Nicolás (2024)
Background: HTLV-1/2 exhibit a widespread distribution globally and are associated with severe clinical manifestations, necessitating precise viral identification for diagnosis. Currently, there are no official diagnostic guidelines, and a variety of published protocols exists. We introduce an enhanced nested real-time PCR technique followed by high-resolution melting (rtPCR-HRM), designed to offer a cost-effective and straightforward tool for the simultaneous identification of both viruses.Methods: The technique was tested in a retrospective, blinded study, involving a total panel of 110 samples, of which 47 were positive for HTLV-1, 12 for HTLV-2, and 51 tested negatives. Additionally, we compared the performance of this technique with a line immunoassay (LIA).Results: The results demonstrate 100 % sensitivity, specificity, and diagnostic accuracy for both viruses. Sensitivity analysis indicated that at least 1 viral copy of HTLV-1 and 14.4 viral copies of HTLV-2 could be reliably detected.Conclusions: Our results indicate that rtPCR-HRM is effective in confirming HTLV-1 and HTLV-2 infection, important in Latin American countries where both viruses circulate. Furthermore, the proposed strategy provides a new tool that can be used to resolve indeterminate cases identified by Western blot, with the added advantage of being faster and simpler than n-PCR and more cost-effective than other probe-based RT-PCRs.